1961
DOI: 10.1149/1.2427973
|View full text |Cite
|
Sign up to set email alerts
|

Cation Diffusion in Cr[sub 2]O[sub 3]

Abstract: On employing a sectioning technique with Cr51 as the tracer, the diffusion of Cr ions in nitrogen‐equilibrated Cr2O3 was determined from 1045° to 1550°C. Volume diffusion coefficients in hot‐pressed compacts of three different impurity levels conform to the expression D=0.137expfalse(−61,100/RTfalse)cm2sec−1 . Additions of 2 normalw/o CeO2 and 1 normalw/normalo Y2O3 do not cause a significant change. Use of lower density sintered compacts provides erroneous results. Conductivity measurements were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
59
2

Year Published

1969
1969
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(79 citation statements)
references
References 9 publications
16
59
2
Order By: Relevance
“…Actually, it was reported that the cation was much more mobile in Cr 2 O 3 than was the anion. 23) The temperature dependence of k p values of chromium obtained in oxygen or in air atmosphere is shown in Fig. 9, comparing the present results with those reported by other groups.…”
Section: Discussionsupporting
confidence: 88%
“…Actually, it was reported that the cation was much more mobile in Cr 2 O 3 than was the anion. 23) The temperature dependence of k p values of chromium obtained in oxygen or in air atmosphere is shown in Fig. 9, comparing the present results with those reported by other groups.…”
Section: Discussionsupporting
confidence: 88%
“…The activation energies for growth were determined to be Q(OST)= 262 ± 33 kJ/mol, Q(AFD)= 218 ± 18 kJ/mol, and Q(GPD)= 285 ± 35 kJ/mol. There is good agreement for Q(OST) with the literature value for Cr 2 O 3 growth of 256 kJ/mol [14], even though TiO 2 grains have been included in the thickness determination.…”
Section: Resultssupporting
confidence: 73%
“…Figure 5 shows a good straight line fit for the isothermal exposure data. The gradient of this line gives an activation energy of ~270 kJ/mol, which is higher than literature values (256 kJ/mol or 61.1 kcal/mol) for Cr 2 O 3 growth [6], although the tests in the current study have been carried out at much lower temperatures. Chen et al [7] reported activation energies of 250, 270 and 300 kJ/mol for nickel disc alloys Udimet 720, Astroloy and Waspaloy, which were determined from isothermal exposures and cyclic oxidation testing at 750-1000ºC.…”
Section: Characterisation Of Oxidation Kineticscontrasting
confidence: 64%